Detailed phenotyping reveals distinct trajectories of cardiovascular function and symptoms with exposure to modern breast cancer therapy. Issue 16 (1st May 2019) - Demissei, Biniyam G.; Finkelman, Brian S.; Hubbard, Rebecca A.; Zhang, Liyong; Smith, Amanda M.; Sheline, Karyn; McDonald, Caitlin; Narayan, Hari K.; Narayan, Vivek; Waxman, Adam J.; Domchek, Susan M.; DeMichele, Angela; et al.
Abstract : Background: Breast cancer therapies are associated with a risk of cardiac dysfunction, most commonly defined by changes in left ventricular ejection fraction (LVEF). Recently, the authors identified 3 classes of LVEF change after exposure to anthracyclines and/or trastuzumab using latent class growth modeling. The objective of the current study was to characterize the clinical, biochemical, and functional profiles associated with LVEF trajectory class membership. Methods: Transthoracic echocardiography and biomarker assessments were performed and questionnaires were administered at standardized intervals in a longitudinal cohort of 314 patients with breast cancer who were treated with anthracyclines and/or trastuzumab. Univariable and multivariable multinomial regression analyses evaluated associations between baseline variables and LVEF trajectory class membership. Generalized estimating equations were used to define mean changes in cardiovascular measures over time within each class. Results: Among the 3 distinct subgroups of LVEF changes identified (stable [class 1]; modest, persistent decline [class 2]; and significant early decline followed by partial recovery [class 3]), higher baseline LVEF, radiotherapy, and sequential therapy with anthracyclines and/or trastuzumab were associated with class 2 or 3 membership. Sustained abnormalities in longitudinal strain and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) were observed in patients in class 2, as were heart failure symptoms. Similar abnormalities were observed in patients in class 3, but there was a trend toward recovery, particularly for longitudinal strain. Conclusions: Patients with modest, persistent LVEF declines experienced sustained abnormalities in imaging and biochemical markers of cardiac function and heart failure symptoms. Further investigation is needed to characterize the long‐term risk of heart failure, particularly in those with modest LVEF declines. Abstract : Modest declines in left ventricular ejection fraction (LVEF) in patients with breast cancer who are treated with cardiotoxic cancer therapy are accompanied by an increased incidence of biochemical and functional abnormalities. This suggests that declines in LVEF that do not reach the conventional thresholds used for the diagnosis of cardiotoxicity could be more clinically important than previously understood.